16.0k views
3 votes
Find g^-1(x)

A
B
C
D

Find g^-1(x) A B C D-example-1

1 Answer

2 votes

Answer:


a. \ g^(-1)=-1 \pm\sqrt{(3)/(x)+1}

Explanation:

A function has an inverse function if and only if passes the Horizontal Line Test for Inverse Functions. This test tells us that a function
f has an inverse function if and only if there is no any horizontal line that intersects the graph of
f at more than one point. So the function is called one-to-one. The graph of
g is shown below. As you can see, this function does not pass the Horizontal Line Test, therefore the inverse is not a function. However, let's find
g^-{1}(x):


g(x)=(3)/(x^2+2x) \\ \\ Substitute \ g(x) \ by \ y \\ \\y=(3)/(x^2+2x) \\ \\ Interchange \ x \ and \ y: \\ \\ x=(3)/(y^2+2y) \\ \\ Solve \ for \ y: \\ \\y^2+2y=(3)/(x) \\ \\ Completing \ square \\ \\y^2+2y\mathbf{+ 1}\mathbf{-1}=(3)/(x) \\ \\(y+1)^2=(3)/(x)+1 \\ \\y+1=\pm\sqrt{(3)/(x)+1} \\ \\ y=-1 \pm\sqrt{(3)/(x)+1}

Finally, substitute
y \ by \ g^(-1):


boxed{g^(-1)=-1 \pm\sqrt{(3)/(x)+1}}

Find g^-1(x) A B C D-example-1
User Aref Karimi
by
5.4k points